Geometry, structures and evolution of the western termination of the Alpine-Pyrenean Orogen reliefs (NW Iberian Peninsula) - Martín González, F.; Heredia, N. (Journal of Iberian Geology, 2011)
The geometry, structures and tectonic evolution of the western termination of the Alpine-Pyrenean Orogen relief onshore and related foreland have been studied. We present the results of structural mapping and detailed outcrop studies of Cenozoic-age structures carried out at the NW Iberian Peninsula. On the basis of this work we propose a new tectonic model for the termination. According to the identified structures, three main regions could be recognised: (1) the Astur-Galaica (AG) region or the western part of the Cantabrian Mountains (CM), characterised by thrusts with a south vergence, which are the continuation of the structures of the Pyrenees, (2) The Galaico-Leoneses Mountains (GLM), characterized by thrusts with a north vergence, and (3) The Rías Baixas-Terra Chá region (RBT) characterized by strike-slip faults with no relevant associated relief but with recent seismic activity, which represents the less deformed Alpine foreland. The western termination of the Alpine-Pyrenean Orogen is formed due to the superposition of two mountain ranges (CM and GLM) and a complex tectonic evolution. The CM were emplaced southwards and subsequently the GLM was emplaced northwards. The western limit of the E-W thrusts of the CM and the associated relief define a N-S-oriented arch-shape structures (Ibias-Ancares and Rúa-Vilalba). Tectonic activity commenced during the Eocene, and in the westernmost areas during the Late Oligocene. The CM south-verging thrust activity ended at the beginning of Late Miocene, although deformation continued in the GLM with north-verging thrusts. The evidence of intense tectonic activity during the Miocene, the western migration and southward transference of tectonic activity and the interaction of two successive deformation fronts, suggests that a re-examination of the tectonic evolution of the northern Iberian microplate during the Alpine Orogeny is necessary.